An island-type coating suitable for the leading edge of a wind turbine blade and a preparation method thereof
By applying island -type coating on the front edge of the wind power blades, the high -hardness island area and the flexible base area are used to solve the problem of easily corrosion of the front edge of the blade, which significantly improves the resistance of rain and erosion. Life and reduced power generation and hidden safety hazards.
Patent Information
- Application Number
- CN202311399340.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-10-25
AI Technical Summary
During high-speed operation, the leading edge of the wind power blade is susceptible to pneumatic friction, aging, rain corrosion, salt spray, sand corrosion and biological erosion, resulting in corrosion and affecting the service life of the blade and power generation efficiency.
The island -type coating is used. The coating structure is divided into base areas and island areas. The hardness of the island area is greater than the base area. Printing techniques form coatings with high anti -rain erosion properties.
It significantly improves the anti -rainfall performance of the front edge of the wind power blades, prolongs the life of the leaves, and reduces the reduction of power generation and hidden safety hazards caused by corrosion.
Smart Images

Figure CN117447904B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of wind power coatings, and in particular relates to an island-type coating suitable for the leading edge of a wind power blade and a preparation method thereof. Background Art
[0002] Blades are the only components of wind turbines that capture wind energy. Their safe and stable operation is the basis for wind turbines to obtain higher wind energy utilization coefficients and economic benefits. However, blade damage is also a common problem in wind farms. Therefore, how to protect blades from damage for a long time is a key technology in the wind power industry. A large number of studies have shown that blade leading edge corrosion is one of the important causes of blade damage.
[0003] The leading edge of the blade (from the tip to the position of 1 / 3 of the blade length) is in a high-speed operation state for a long time, and is easily affected by factors such as aerodynamic friction, aging, rain erosion, salt spray, sand erosion and biological erosion. If not protected, it will generally begin to corrode after 0.5-2 years of operation, but the service life of the blade is generally required to be greater than 20 years; on the other hand, the corrosion of the leading edge of the blade will have an adverse effect on the aerodynamic performance. Mild leading edge corrosion can cause a 5% reduction in annual power generation, and severe leading edge corrosion can cause a maximum reduction of 25% in annual power generation. At the same time, if the leading edge of the blade is severely corroded, it will greatly increase the breakage and fracture of the blade and deepen the degree of damage to the blade after being struck by lightning, posing a threat to the safe operation of the unit.
[0004] In order to slow down the corrosion of the leading edge of the blade, the existing methods are mostly to directly use a protective film on the outside of the blade, or to add a coating on the leading edge of the blade, and to improve the corrosion resistance of the leading edge of the blade by adjusting the formula and composition of the coating. However, in the above methods, the protective film added to the outside of the blade is prone to aging, and will be damaged and gradually lose its protective effect after the unit has been in operation for 3-5 years. It is difficult to further reduce the force on the blade surface by adjusting the composition of the blade coating, so that the impact force on the blade is still relatively large. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and to provide an island-type coating suitable for the leading edge of a wind turbine blade and a preparation method thereof, so as to solve the problem in the prior art that the blades are subjected to continuous large impact forces during operation, making the blades susceptible to corrosion and increasing the degree of damage.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] An island-type coating suitable for the leading edge of a wind turbine blade, comprising a base area and an island area, wherein the area of the base area is larger than that of the island area, the island area is dispersedly arranged in the base area, and the hardness of the island area is greater than that of the base area;
[0008] The base region is composed of component A and component B; component A is composed of polyetheramine, polyaspartic acid ester resin and diisocyanate, component B is composed of solvent-based ceramics and substance C, and substance C is a mixture of isocyanate and blocked isocyanate;
[0009] The composition material of the island area is the same as that of the base area, and solvent-based ceramics and substance C are added to component A of the island area.
[0010] A further improvement of the present invention is:
[0011] Preferably, the average diameter of the island region is 200-300 μm, and the distance between adjacent islands is 200-350 μm.
[0012] Preferably, the area of the island region in the coating is 20-30%.
[0013] A method for preparing the above-mentioned island-in-sea coating comprises the following steps:
[0014] The base area is printed by the base area print head, and the island area is printed by the island area print head, the island area print head follows the base area print head for printing, and laser curing is performed after the base area printing and the island area printing;
[0015] Both the base and island regions were printed by pressure extrusion, and the printer's component A and component B extrusion feed ratio was 1:1 to 2.2:1.
[0016] Preferably, the printing interval between the island area print head and the base area print head is less than 15 seconds.
[0017] Preferably, the laser curing time of the base region is 10 to 15 seconds, and the laser curing time of the island region is 20 to 40 seconds.
[0018] Preferably, in the base region, the preparation process of component A is: weighing polyetheramine and polyaspartic acid ester resin respectively, vacuum drying, introducing nitrogen to cool, dripping diisocyanate, adding dimethyl sulfoxide after reaction and stirring to obtain component A;
[0019] The preparation process of component B is as follows: solvent-based ceramic and substance C are mixed in a mass ratio of 0.1 to 0.35:1, and component B is obtained after stirring.
[0020] Preferably, in the island region, the preparation process of component A is to weigh polyetheramine and polyaspartic acid ester resin respectively, vacuum dry them, introduce nitrogen to cool them down, drop diisocyanate and a mixture of solvent-based ceramics and substance C, add dimethyl sulfoxide after reaction and stir to obtain component A; wherein the mixing mass ratio of solvent-based ceramics and substance C is 0.1 to 0.2:1;
[0021] The preparation process of component B is to mix the solvent-based ceramic and the substance C in a mass ratio of 0.3 to 0.6:1, and then stir to obtain component B.
[0022] Preferably, the molar ratio of -NCO in substance C to -NH in the polyaspartic acid ester resin in component A is (0.9-1.2):1.
[0023] Preferably, the preparation method of the solvent-based ceramic is to stir triethoxysilane, dimethyl sulfoxide and a catalyst to react, then add ethoxyphenyl silicone resin, stir and then add functional filler to obtain the solvent-based ceramic.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention discloses an island-type coating suitable for the leading edge of a wind turbine blade. The structure of the coating is divided into a base area and an island area. The island area is dispersed in the base area, and the hardness of the island area is greater than that of the base area. The base area, as a sea area with good flexibility, can disperse the stress generated during the impact process, and the island area, as an area with a certain hardness, can effectively resist the high-frequency impact of raindrops without being damaged. The interaction between the "sea" and "island" structures can significantly improve the anti-rain erosion performance. The island structure can mobilize the molecular network of the coating matrix resin to undergo many energy-consuming processes such as orientation, stretching, deformation, cavitation, and microcracks, thereby avoiding the damage of the coating and improving the performance of resisting raindrop impact. In the final printing process of the coating, polyetheramine, diisocyanate, and polyaspartic acid ester resin are used as component A, and component B is made of isocyanate, blocked isocyanate and solvent-based ceramics as raw materials. According to the different hardness of the base area and the island area, the amount of solvent-based ceramic added is different; as the amount of solvent-based ceramic increases, the hardness is higher; so that the above-mentioned coating can achieve different functions.
[0026] Furthermore, in the coating, polyetheramine is a hydrophilic monomer, which makes the system have good hydrophilicity, which is conducive to forming a water film on the leading edge of the wind turbine blade, effectively buffering the impact of raindrops on the leading edge of the wind turbine blade. Diisocyanate can extend the chain of the system to increase the molecular weight of the product, thereby increasing the solid content of the polyurea base material and improving the stability of the solution. Furthermore, the -NCO group can react with the -NH group on the polyaspartic acid ester to generate a urea group, thereby reducing the reactivity of the system. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the coating structure of the present invention;
[0028] Figure 2 It is a schematic diagram of the printing direction of the present invention;
[0029] Among them: 1-base area; 2-island area; 3-island area print head; 4-base area print head. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments:
[0031] See also Figure 1 The present invention discloses, on the one hand, an island-type coating suitable for the leading edge of a wind turbine blade. The structure of the coating is divided into a base area 1 and an island area 2. The island area 2 is dispersed in the base area 1, and the hardness of the island area 2 is greater than that of the base area 1.
[0032] Specifically, the shape and specific position of the island area 2 can be adjusted according to the specific position of the coating.
[0033] The size of the island region 2 is: an average diameter of 200 to 300 μm, and a spacing of 200 to 350 μm.
[0034] Preferably, the shape of the island area 2 is a regular shape, and the distances between adjacent island areas 2 are equal.
[0035] Preferably, the island region 2 occupies 20% to 30% of the area.
[0036] In some embodiments of the present invention, a soluble ceramic precursor resin is added to a polyurea resin matrix to form a homogeneous phase. After curing, the ceramic precursor resin forms a hard ceramic phase to constitute the island region 2, and the polyurea resin forms a base region 1 with good flexibility.
[0037] In some embodiments of the present invention, a method for preparing a base region 1 is disclosed, comprising the following steps:
[0038] Step 1, preparing slurry of base area 1
[0039] Step 1.1, preparation of component A
[0040] (1) Weigh polyetheramine and polyaspartic acid ester resin according to a set ratio, place them in a four-necked flask for vacuum drying, and the vacuum drying conditions are: 100 to 105° C., -0.04 to -0.07 MPa, and time is 1 to 1.5 h.
[0041] The polyaspartic acid ester resin is a mixture of F420 and F520, wherein the molar ratio of the polyaspartic acid ester resin F420 to the polyaspartic acid ester resin F520 is 4-5:1.
[0042] The polyetheramine is a mixture of any one or more of polyetheramine M230, polyetheramine M1000 or polyetheramine 2000.
[0043] In some embodiments, the mass ratio of the polyaspartic acid ester resin to the polyetheramine is (3-8):1.
[0044] (2) Weigh the diisocyanate according to the above ratio and place it in a constant pressure titration funnel.
[0045] The diisocyanate is any one or more mixtures of isophorone diisocyanate, hexamethylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.
[0046] In some embodiments, the molar ratio of polyetheramine to diisocyanate is 1:(1-1.3).
[0047] (3) The four-necked flask containing the polyetheramine and the polyaspartic acid ester resin in step (1) is taken out from the vacuum drying oven, nitrogen is introduced into the flask while the stirrer is turned on, and the temperature is lowered to 30-50° C.
[0048] (4) Open the constant pressure titration funnel in step (2) and add diisocyanate to the four-necked flask at a uniform rate for 1 to 1.5 hours.
[0049] (5) After the dripping is completed, rinse the constant pressure titration funnel with a certain amount of dipropylene glycol dimethyl ether and drip it into the four-necked flask, raise the temperature to 50-70°C, and react at a constant temperature for 2-3 hours.
[0050] (6) Change the constant pressure titration funnel and slowly add dimethyl sulfoxide to the reaction product of step (5) while stirring. The addition time is 0.5 to 1 h, the stirring speed is 1000 to 1300 r / min, and the stirring time is 0.3 to 0.5 h to obtain component A.
[0051] Step 1.2, preparation of component B
[0052] Component B is composed of solvent-based ceramic and substance C mixed and stirred in a mass ratio of 0.1 to 0.35:1. Substance C is a mixture of isocyanate and blocked isocyanate, wherein the mass ratio of isocyanate to blocked isocyanate is 1:2 to 1:4.
[0053] Specifically, for substance C, based on n(—NCO):n(—NH)=(0.9-1.2):1, the amount of —NCO in substance C is calculated according to the weight of —NH in the polyaspartic acid ester resin in component A, and then the amount of substance C is obtained.
[0054] Specifically, the preparation method of solvent-based ceramics includes the following steps:
[0055] (1) 100 parts of octamethylcyclotetrasiloxane are placed in a beaker, and the beaker is placed in an oil bath; 0.2-0.3 parts of potassium hydroxide are slowly added into the beaker through a funnel, and the mixture is heated to 115-120° C. with stirring. After the potassium hydroxide is completely dissolved, the mixture is cooled to room temperature to obtain a transparent potassium hydroxide alkali gel as a catalyst.
[0056] (2) Weigh triethoxysilane, ethoxyphenyl silicone resin and functional filler of the ceramic respectively, the mass ratio of the three in the ceramic is 1:1:1.5, and weigh the catalyst component D in step (1), the mass content of which is 0.1-0.2% of the total mass.
[0057] Among them, triethoxysilane as a silane coupling agent can undergo a sol reaction to generate a dense three-dimensional network cross-linked structure, and ethoxyphenyl silicone resin as a multifunctional silicone resin can participate in the sol-gel reaction of the silane coupling agent to increase the strength and toughness of the three-dimensional cross-linked structure; functional fillers include (reinforcement, toughening, thermal conductivity, wear resistance, anti-ablation, etc.) fillers, leveling agents, dispersants, etc.
[0058] The mass ratio of triethoxysilane, ethoxyphenyl silicone resin and functional filler is 1:1:1.5, and the mass fraction of the catalyst in the ceramic is 0.1-0.2%.
[0059] (3) Place triethoxysilane, dimethyl sulfoxide and the catalyst in a 50°C water bath and stir for 0.5 to 1 hour at a stirring speed of 100 to 180 r / min.
[0060] (4) Adding ethoxyphenyl silicone resin to the reaction product in step (3), stirring at room temperature for 2 to 2.5 hours at a stirring speed of 400 to 560 r / min.
[0061] (5) Add nano-titanium dioxide, acrylic acid and organic amine to the reaction product of step (4), stir at room temperature for 1 to 1.5 hours at a stirring speed of 400 to 500 r / min to obtain a ceramic base material.
[0062] Step 2, preparing the slurry of the island area 2, comprises the following steps:
[0063] Step 2.1, preparation of component A
[0064] The preparation process is the same as the preparation steps 1 to 3 of the base region 1 described above, except that in step (2) of preparing component A in step 1, solvent-based ceramics and substance C are also added to the constant pressure titration funnel. The amount of -NCO in substance C is calculated based on n(-NCO):n(-NH)=(0.9-1.2):1, and the amount of -NCO in substance C is obtained according to the weight of -NH in the polyaspartic acid ester resin in component A, thereby obtaining the dosage of substance C. The mass ratio of the added solvent-based ceramics to substance C is 0.1-0.2:1.
[0065] The solvent-based ceramic is added to step (2) so that during the reaction of diisocyanate with polyetheramine and polyaspartic acid ester resin to form a cross-linked structure, the solvent-based ceramic can be evenly distributed into the polyurea base material as a reinforcing component, making the "island" structure in the sea island more "hard".
[0066] Step 2.2, when preparing component B, the mass ratio of solvent-based ceramic to substance C is 0.3-0.6:1.
[0067] The remaining steps are the same as the above-mentioned process of preparing the base region 1.
[0068] In step 1 and step 2, the reaction rate between the amino group of polyaspartic acid ester resin and isocyanate is extremely fast, which can easily cause nozzle clogging and make 3D printing difficult. This process introduces solvent-based ceramic components and blocked isocyanate to adjust the curing rate of the amino group and isocyanate and the viscosity of the system to achieve two-component polyurea direct writing 3D printing.
[0069] Step 3, 3D Printing
[0070] See also Figure 2 When printing base area 1 and island area 2, the straight pen 3D printing method is adopted, and the two 3D printer heads work at the same time. After modeling, the base area printing head 4 is used to print the base area 1 first (the base area 1 contains less ceramic and solidifies slowly), and then the island area printing head 3 is used to print the island area 2 part (so that the boundary part can be connected and there will be no obvious interface feeling). The two heads work at the same time, and the printing time of the two heads does not exceed 15s.
[0071] The components A and B prepared in step 1 are used to print the base area 1 through the base area print head 4. Components A and B are pumped to the printing cavity for mixing, printed by pressure extrusion, and laser cured, and this operation is repeated until the printing is completed. Among them, the extrusion feed ratio of the printer is between 1:1 and 2.2:1 in terms of mass fraction, and the printing speed of the printer is: 200-1200mm / min. After the base area 1 is printed by the first printer, laser heating is used for curing for 10 to 15s to partially unblock the blocked isocyanate, resulting in an increase in viscosity, which can maintain the shape on the substrate.
[0072] At the same time, component A and component B are prepared in step 2 and island area 2 is printed through island area print head 3. After the second printer extrude and prints part of island area 2, the laser scans the entire complete area for 20 to 40 seconds to completely release the blocked isocyanate, so that the "island" and "sea" parts are combined and solidified without producing an obvious interface, forming a whole, thereby avoiding stress cracking caused by raindrops hitting this place.
[0073] The following is further described in conjunction with specific embodiments.
[0074] Example 1
[0075] Step 1, preparing slurry of base area 1
[0076] Step 1.1, preparation of component A
[0077] (1) Weigh polyetheramine M230 and polyaspartic acid ester resin according to a set ratio, and place them in a four-necked flask for vacuum drying. The vacuum drying conditions are: 100°C, -0.05MPa, and time for 1 hour.
[0078] The polyaspartic acid ester resin is a mixture of F420 and F520, wherein the molar ratio of the polyaspartic acid ester resin 420 to the polyaspartic acid ester resin F520 is 1:1.
[0079] In some embodiments, the mass ratio of the polyaspartic acid ester resin to the polyetheramine is 5:1.
[0080] (2) Weigh the diisocyanate according to the above ratio and place it in a constant pressure titration funnel.
[0081] The diisocyanate is isophorone diisocyanate, and the molar ratio of the polyetheramine to the diisocyanate is 1:1.
[0082] (3) The four-necked flask containing the polyetheramine and the polyaspartic acid ester resin in step (1) was taken out from the vacuum drying oven, nitrogen was introduced into the flask while the stirrer was turned on, and the temperature was lowered to 40°C.
[0083] (4) Open the constant pressure titration funnel in step (2) and add diisocyanate to the four-necked flask at a uniform rate for 1 hour.
[0084] (5) After the dripping is completed, rinse the constant pressure titration funnel with a certain amount of dipropylene glycol dimethyl ether and drip it into the four-necked flask, raise the temperature to 60°C, and react at the constant temperature for 2 hours.
[0085] (6) Change the constant pressure titration funnel and slowly add dimethyl sulfoxide to the reaction product of step (5) and start stirring. The dropping time is 1 hour, the stirring speed is 1000 r / min, and the stirring time is 0.5 hour to obtain component A.
[0086] Step 1.2, preparation of component B
[0087] Component B is composed of solvent-based ceramic and substance C mixed and stirred in a mass ratio of 0.2:1. Substance C is a mixture of isocyanate and blocked isocyanate, wherein the mass ratio of isocyanate to blocked isocyanate is 1:2.
[0088] Specifically, for substance C, based on n(—NCO):n(—NH)=1:1, the amount of —NCO in substance C is calculated according to the weight of —NH in the polyaspartic acid ester resin in component A, and then the amount of substance C is obtained.
[0089] Specifically, the preparation method of solvent-based ceramics includes the following steps:
[0090] (1) 100 parts of octamethylcyclotetrasiloxane are placed in a beaker, and the beaker is placed in an oil bath; 0.2 parts of potassium hydroxide is slowly added into the beaker through a funnel, and the mixture is heated to 120° C. with stirring. After the potassium hydroxide is completely dissolved, the mixture is cooled to room temperature to obtain a transparent potassium hydroxide alkali gel as a catalyst.
[0091] (2) Weigh triethoxysilane, ethoxyphenyl silicone resin and functional filler of the ceramic respectively, the mass ratio of the three in the ceramic is 1:1:1.5, and weigh the catalyst component D in step (1), the mass content of which is 0.1% of the total mass.
[0092] (3) Place triethoxysilane, dimethyl sulfoxide and the catalyst in a 50°C water bath and stir for 1 h at a stirring speed of 150 r / min.
[0093] (4) Adding ethoxyphenyl silicone resin to the reaction product in step (3), stirring at room temperature for 2 hours at a stirring speed of 500 r / min.
[0094] (5) Add nano-titanium dioxide, acrylic acid and organic amine to the reaction product of step (4), stir at room temperature for 1 hour at a stirring speed of 500 r / min to obtain a ceramic base material.
[0095] Step 2: Prepare slurry for island 2
[0096] Step 2.1, the process of preparing component A is the same as the process of preparing the slurry of base region 1 in the above step 1.1, but solvent-based ceramic and substance C are added in a mass ratio of 0.15:1.
[0097] Step 2.2, the process of preparing component B is the same as the process of preparing the slurry of island area 2 in the above step 1.2, but in this process, component B is composed of solvent-based ceramic and substance C mixed and stirred at a mass ratio of 0.5:1.
[0098] Step 3, using the base area print head 4 to print the base area 1, and using the island area print head 3 to print the island area 2. The A and B components are pumped to the printing cavity for mixing, and then printed by pressure extrusion, and then cured by laser. This operation is repeated until the printing is completed. In terms of mass fraction, the extrusion feed ratio of the printer is between 2:1. The printing speed of the printer is: 1000mm / min.
[0099] The laser curing time after printing the base area 1 is 10 seconds, the laser curing time after printing the island area 2 is 20 seconds, and the interval between the two print heads is 12 seconds.
[0100] Example 2
[0101] Step 1, preparing slurry of base area 1
[0102] Step 1.1, preparation of component A
[0103] (1) Weigh polyetheramine M1000 and polyaspartic acid ester resin according to a set ratio, and place them in a four-necked flask for vacuum drying. The vacuum drying conditions are: 105° C., -0.04 MPa, and the time is 1.2 h.
[0104] The polyaspartic acid ester resin is a mixture of F420 and F520, wherein the molar ratio of the polyaspartic acid ester resin 420 to the polyaspartic acid ester resin F520 is 1:1.
[0105] In some embodiments, the mass ratio of the polyaspartic acid ester resin to the polyetheramine is 6:1.
[0106] (2) Weigh the diisocyanate according to the above ratio and place it in a constant pressure titration funnel.
[0107] The diisocyanate is hexamethylene diisocyanate, and the molar ratio of the polyetheramine to the diisocyanate is 1:1.2.
[0108] (3) The four-necked flask containing the polyetheramine and the polyaspartic acid ester resin in step (1) was taken out from the vacuum drying oven, nitrogen was introduced into the flask while the stirrer was turned on, and the temperature was lowered to 50° C.
[0109] (4) Open the constant pressure titration funnel in step (2) and add diisocyanate to the four-necked flask at a constant rate for 1.5 hours.
[0110] (5) After the dripping is completed, rinse the constant pressure titration funnel with a certain amount of dipropylene glycol dimethyl ether and drip it into the four-necked flask, raise the temperature to 50°C, and react at the constant temperature for 3 hours.
[0111] (6) Change the constant pressure titration funnel and slowly add dimethyl sulfoxide to the reaction product of step (5) and start stirring. The dropping time is 0.5 h, the stirring speed is 1300 r / min, and the stirring time is 0.3 h to obtain component A.
[0112] Step 1.2, preparation of component B
[0113] Component B is composed of solvent-based ceramic and substance C mixed and stirred in a mass ratio of 0.35:1. Substance C is a mixture of isocyanate and blocked isocyanate, wherein the mass ratio of isocyanate to blocked isocyanate is 1:3.
[0114] Specifically, for substance C, based on n(—NCO):n(—NH)=1.2:1, the amount of —NCO in substance C is calculated according to the weight of —NH in the polyaspartic acid ester resin in component A, and then the amount of substance C is obtained.
[0115] Specifically, the preparation method of solvent-based ceramics includes the following steps:
[0116] (1) 100 parts of octamethylcyclotetrasiloxane are placed in a beaker, and the beaker is placed in an oil bath; 0.25 parts of potassium hydroxide are slowly added into the beaker through a funnel, and the mixture is heated to 115° C. with stirring. After the potassium hydroxide is completely dissolved, the mixture is cooled to room temperature to obtain a transparent potassium hydroxide alkali gel as a catalyst.
[0117] (2) Weigh triethoxysilane, ethoxyphenyl silicone resin and functional filler of the ceramic respectively, the mass ratio of the three in the ceramic is 1:1:1.5, and weigh the catalyst component D in step (1), the mass content of which is 0.2% of the total mass.
[0118] (3) Place triethoxysilane, dimethyl sulfoxide and the catalyst in a 50°C water bath and stir for 0.5 h at a stirring speed of 170 r / min.
[0119] (4) Adding ethoxyphenyl silicone resin to the reaction product in step (3), stirring at room temperature for 2.5 hours at a stirring speed of 400 r / min.
[0120] (5) Add nano-titanium dioxide, acrylic acid and organic amine to the reaction product of step (4), stir at room temperature for 1 hour at a stirring speed of 500 r / min to obtain a ceramic base material.
[0121] Step 2: Prepare slurry for island 2
[0122] Step 2.1, the process of preparing component A is the same as the process of preparing the slurry of base area 1 in the above step 1.1, but solvent-based ceramic and substance C are added in a mass ratio of 0.2:1.
[0123] Step 2.2, the process of preparing component B is the same as the process of preparing the slurry of island area 2 in the above step 1.2, but in this process, component B is composed of solvent-based ceramic and substance C mixed and stirred at a mass ratio of 0.6:1.
[0124] Step 3, using the base area print head 4 to print the base area 1, and using the island area print head 3 to print the island area 2. The A and B components are pumped to the printing cavity for mixing, and then printed by pressure extrusion, and laser curing is used. This operation is repeated until the printing is completed. In terms of mass fraction, the extrusion feed ratio of the printer is between 1:1. The printing speed of the printer is: 200mm / min.
[0125] The laser curing time after printing the base area 1 is 15 seconds, the laser curing time after printing the island area 2 is 40 seconds, and the interval between the two print heads is 15 seconds.
[0126] Example 3
[0127] Step 1, preparing slurry of base area 1
[0128] Step 1.1, preparation of component A
[0129] (1) Weigh polyetheramine 2000 and polyaspartic acid ester resin according to the set ratio, and place them in a four-necked flask for vacuum drying. The vacuum drying conditions are: 102°C, -0.07MPa, and the time is 1.5h.
[0130] The polyaspartic acid ester resin is a mixture of F420 and F520, wherein the molar ratio of the polyaspartic acid ester resin to the polyaspartic acid ester resin F520 is 1:1.
[0131] In some embodiments, the mass ratio of the polyaspartic acid ester resin to the polyetheramine is 3:1.
[0132] (2) Weigh the diisocyanate according to the above ratio and place it in a constant pressure titration funnel.
[0133] The diisocyanate is 4,4'-dicyclohexylmethane diisocyanate, and the molar ratio of the polyetheramine to the diisocyanate is 1:1.3.
[0134] (3) The four-necked flask containing the polyetheramine and the polyaspartic acid ester resin in step (1) was taken out from the vacuum drying oven, nitrogen was introduced into the flask while the stirrer was turned on, and the temperature was lowered to 30° C.
[0135] (4) Open the constant pressure titration funnel in step (2) and add diisocyanate to the four-necked flask at a constant rate for 1.2 h.
[0136] (5) After the dripping is completed, rinse the constant pressure titration funnel with a certain amount of dipropylene glycol dimethyl ether and drip it into the four-necked flask, raise the temperature to 70°C, and react at the constant temperature for 2.5 hours.
[0137] (6) Change the constant pressure titration funnel and slowly add dimethyl sulfoxide to the reaction product of step (5) and start stirring. The dropping time is 0.5 h, the stirring speed is 1100 r / min, and the stirring time is 0.4 h to obtain component A.
[0138] Step 1.2, preparation of component B
[0139] Component B is composed of solvent-based ceramic and substance C mixed and stirred in a mass ratio of 0.1:1. Substance C is a mixture of isocyanate and blocked isocyanate, wherein the mass ratio of isocyanate to blocked isocyanate is 1:4.
[0140] Specifically, for substance C, based on n(—NCO):n(—NH)=0.9:1, the amount of —NCO in substance C is calculated according to the weight of —NH in the polyaspartic acid ester resin in component A, and then the amount of substance C is obtained.
[0141] Specifically, the preparation method of solvent-based ceramics includes the following steps:
[0142] (1) 100 parts of octamethylcyclotetrasiloxane are placed in a beaker, and the beaker is placed in an oil bath; 0.3 parts of potassium hydroxide is slowly added into the beaker through a funnel, and the mixture is heated to 118° C. with stirring. After the potassium hydroxide is completely dissolved, the mixture is cooled to room temperature to obtain a transparent potassium hydroxide alkali gel as a catalyst.
[0143] (2) Weigh triethoxysilane, ethoxyphenyl silicone resin and functional filler of the ceramic respectively, the mass ratio of the three in the ceramic is 1:1:1.5, and weigh the catalyst component D in step (1), the mass content of which is 0.15% of the total mass.
[0144] (3) Place triethoxysilane, dimethyl sulfoxide and the catalyst in a 50°C water bath and stir for 0.8 h at a stirring speed of 180 r / min.
[0145] (4) Adding ethoxyphenyl silicone resin to the reaction product in step (3), stirring at room temperature for 2.2 hours at a stirring speed of 560 r / min.
[0146] (5) Add nano-titanium dioxide, acrylic acid and organic amine to the reaction product of step (4), stir at room temperature for 1 hour at a stirring speed of 500 r / min to obtain a ceramic base material.
[0147] Step 2: Prepare slurry for island 2
[0148] Step 2.1, the process of preparing component A is the same as the process of preparing the slurry of base region 1 in the above step 1.1, but solvent-based ceramic and substance C are added in a mass ratio of 0.1:1.
[0149] Step 2.2, the process of preparing component B is the same as the process of preparing the slurry of island area 2 in the above step 1.2, but in this process, component B is composed of solvent-based ceramic and substance C mixed and stirred at a mass ratio of 0.35:1.
[0150] Step 3, using the base area print head 4 to print the base area 1, and using the island area print head 3 to print the island area 2. The A and B components are pumped to the printing cavity for mixing, and then printed by pressure extrusion, and laser curing is used. This operation is repeated until the printing is completed. In terms of mass fraction, the extrusion feed ratio of the printer is between 2.2:1. The printing speed of the printer is: 1200mm / min.
[0151] The laser curing time after printing the base area 1 is 12 seconds, the laser curing time after printing the island area 2 is 30 seconds, and the interval between the two print heads is 15 seconds.
[0152] Example 4
[0153] Step 1, preparing slurry of base area 1
[0154] Step 1.1, preparation of component A
[0155] (1) Weigh polyetheramine M230 and polyaspartic acid ester resin according to a set ratio, and place them in a four-necked flask for vacuum drying. The vacuum drying conditions are: 103° C., -0.06 MPa, and time for 1 h.
[0156] The polyaspartic acid ester resin is a mixture of F420 and F520, wherein the molar ratio of the polyaspartic acid ester resin to the polyaspartic acid ester resin F520 is 1:1.
[0157] In some embodiments, the mass ratio of the polyaspartic acid ester resin to the polyetheramine is 8:1.
[0158] (2) Weigh the diisocyanate according to the above ratio and place it in a constant pressure titration funnel.
[0159] The diisocyanate is isophorone diisocyanate, and the molar ratio of the polyetheramine to the diisocyanate is 1:1.1.
[0160] (3) The four-necked flask containing the polyetheramine and the polyaspartic acid ester resin in step (1) was taken out from the vacuum drying oven, nitrogen was introduced into the flask while the stirrer was turned on, and the temperature was lowered to 35° C.
[0161] (4) Open the constant pressure titration funnel in step (2) and add diisocyanate to the four-necked flask at a constant rate for 1.3 h.
[0162] (5) After the dripping is completed, rinse the constant pressure titration funnel with a certain amount of dipropylene glycol dimethyl ether and drip it into the four-necked flask, raise the temperature to 55°C, and react at this constant temperature for 2 hours.
[0163] (6) Change the constant pressure titration funnel and slowly add dimethyl sulfoxide to the reaction product of step (5) and start stirring. The dropping time is 1 hour, the stirring speed is 1200 r / min, and the stirring time is 0.5 hour to obtain component A.
[0164] Step 1.2, preparation of component B
[0165] Component B is composed of solvent-based ceramic and substance C mixed and stirred in a mass ratio of 0.15:1. Substance C is a mixture of isocyanate and blocked isocyanate, wherein the mass ratio of isocyanate to blocked isocyanate is 1:3.
[0166] Specifically, for substance C, based on n(—NCO):n(—NH)=1.1:1, the amount of —NCO in substance C is calculated according to the weight of —NH in the polyaspartic acid ester resin in component A, and then the amount of substance C is obtained.
[0167] Specifically, the preparation method of solvent-based ceramics includes the following steps:
[0168] (6) 100 parts of octamethylcyclotetrasiloxane are placed in a beaker, and the beaker is placed in an oil bath; 0.2 parts of potassium hydroxide is slowly added into the beaker through a funnel, and the mixture is heated to 120° C. with stirring. After the potassium hydroxide is completely dissolved, the mixture is cooled to room temperature to obtain a transparent potassium hydroxide alkali gel as a catalyst.
[0169] (7) Weigh triethoxysilane, ethoxyphenyl silicone resin and functional filler of the ceramic respectively, the mass ratio of the three in the ceramic is 1:1:1.5, and weigh the catalyst component D in step (1), the mass content of which is 0.15% of the total mass.
[0170] (8) Place triethoxysilane, dimethyl sulfoxide and the catalyst in a 50°C water bath and stir for 1 h at a stirring speed of 100 r / min.
[0171] (9) Adding ethoxyphenyl silicone resin to the reaction product in step (3), stirring at room temperature for 2.3 hours at a stirring speed of 450 r / min.
[0172] (10) Add nano-titanium dioxide, acrylic acid and organic amine to the reaction product of step (4), stir at room temperature for 1.5 hours at a stirring speed of 400 r / min to obtain a ceramic base material.
[0173] Step 2: Prepare slurry for island 2
[0174] Step 2.1, the process of preparing component A is the same as the process of preparing the slurry of base region 1 in the above step 1.1, but solvent-based ceramic and substance C are added in a mass ratio of 0.15:1.
[0175] Step 2.2, the process of preparing component B is the same as the process of preparing the slurry of island area 2 in the above step 1.2, but in this process, component B is composed of solvent-based ceramic and substance C mixed and stirred at a mass ratio of 0.5:1.
[0176] Step 3, using the base area print head 4 to print the base area 1, and using the island area print head 3 to print the island area 2. The A and B components are pumped to the printing cavity for mixing, and then printed by pressure extrusion, and then cured by laser. This operation is repeated until the printing is completed. In terms of mass fraction, the extrusion feed ratio of the printer is between 1.5:1. The printing speed of the printer is: 1500mm / min.
[0177] The laser curing time after printing the base area 1 is 10 seconds, the laser curing time after printing the island area 2 is 25 seconds, and the interval between the two print heads is 14 seconds.
[0178] Example 5
[0179] Step 1, preparing slurry of base area 1
[0180] Step 1.1, preparation of component A
[0181] (1) Weigh polyetheramine M230 and polyaspartic acid ester resin according to a set ratio, and place them in a four-necked flask for vacuum drying. The vacuum drying conditions are: 104° C., -0.05 MPa, and the time is 1.3 h.
[0182] The polyaspartic acid ester resin is a mixture of F420 and F520, wherein the molar ratio of the polyaspartic acid ester resin to the polyaspartic acid ester resin F520 is 1:1.
[0183] In some embodiments, the mass ratio of the polyaspartic acid ester resin to the polyetheramine is 7:1.
[0184] (2) Weigh the diisocyanate according to the above ratio and place it in a constant pressure titration funnel.
[0185] The diisocyanate is isophorone diisocyanate, and the molar ratio of the polyetheramine to the diisocyanate is 1:1.
[0186] (3) The four-necked flask containing the polyetheramine and the polyaspartic acid ester resin in step (1) was taken out from a vacuum drying oven, nitrogen was introduced into the flask while the stirrer was turned on, and the temperature was lowered to 45° C.
[0187] (4) Open the constant pressure titration funnel in step (2) and add diisocyanate to the four-necked flask at a constant rate for 1.4 h.
[0188] (5) After the dripping is completed, rinse the constant pressure titration funnel with a certain amount of dipropylene glycol dimethyl ether and drip it into the four-necked flask, raise the temperature to 65°C, and react at the constant temperature for 3 hours.
[0189] (6) Change the constant pressure titration funnel and slowly add dimethyl sulfoxide to the reaction product of step (5) and start stirring. The dropping time is 0.5 h, the stirring speed is 1200 r / min, and the stirring time is 0.4 h to obtain component A.
[0190] Step 1.2, preparation of component B
[0191] Component B is composed of solvent-based ceramic and substance C mixed and stirred in a mass ratio of 0.3:1. Substance C is a mixture of isocyanate and blocked isocyanate, wherein the mass ratio of isocyanate to blocked isocyanate is 1:2.
[0192] Specifically, for substance C, based on n(—NCO):n(—NH)=1:1, the amount of —NCO in substance C is calculated according to the weight of —NH in the polyaspartic acid ester resin in component A, and then the amount of substance C is obtained.
[0193] Specifically, the preparation method of solvent-based ceramics includes the following steps:
[0194] (11) 100 parts of octamethylcyclotetrasiloxane are placed in a beaker, and the beaker is placed in an oil bath; 0.3 parts of potassium hydroxide is slowly added into the beaker through a funnel, and the mixture is heated to 115° C. with stirring. After the potassium hydroxide is completely dissolved, the mixture is cooled to room temperature to obtain a transparent potassium hydroxide gel as a catalyst.
[0195] (12) Weigh triethoxysilane, ethoxyphenyl silicone resin and functional filler of the ceramic respectively, the mass ratio of the three in the ceramic is 1:1:1.5, and weigh the catalyst component D in step (1), the mass content of which is 0.15% of the total mass.
[0196] (13) Place triethoxysilane, dimethyl sulfoxide and the catalyst in a 50°C water bath and stir for 0.8 h at a stirring speed of 160 r / min.
[0197] (14) Add ethoxyphenyl silicone resin to the reaction product in step (3), and stir at room temperature for 2.1 hours at a stirring speed of 550 r / min.
[0198] (15) Add nano-titanium dioxide, acrylic acid and organic amine to the reaction product of step (4), stir at room temperature for 1.2 hours at a stirring speed of 450 r / min to obtain a ceramic base material.
[0199] Step 2: Prepare slurry for island 2
[0200] Step 2.1, the process of preparing component A is the same as the process of preparing the slurry of base region 1 in the above step 1.1, but solvent-based ceramic and substance C are added in a mass ratio of 0.15:1.
[0201] Step 2.2, the process of preparing component B is the same as the process of preparing the slurry of island area 2 in the above step 1.2, but in this process, component B is composed of solvent-based ceramic and substance C mixed and stirred at a mass ratio of 0.5:1.
[0202] Step 3, using the base area print head 4 to print the base area 1, and using the island area print head 3 to print the island area 2. The A and B components are pumped to the printing cavity for mixing, and then printed by pressure extrusion, and then cured by laser. This operation is repeated until the printing is completed. In terms of mass fraction, the extrusion feed ratio of the printer is between 2:1. The printing speed of the printer is: 500mm / min.
[0203] The laser curing time after printing the base area 1 is 13 seconds, the laser curing time after printing the island area 2 is 35 seconds, and the interval between the two print heads is 15 seconds.
[0204] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An island-in-the-sea coating suitable for the leading edge of a wind turbine blade, characterized in that: It comprises a base region (1) and an island region (2), the area of the base region (1) is larger than the area of the island region (2), the island region (2) is dispersedly arranged in the base region (1), and the hardness of the island region (2) is greater than the hardness of the base region (1); The base region (1) is composed of component A and component B; component A is composed of polyetheramine, polyaspartic acid ester resin and diisocyanate, component B is composed of solvent-based ceramic and substance C, and substance C is a mixture of isocyanate and blocked isocyanate; The composition material of the island region (2) is the same as that of the base region (1), and solvent-based ceramic and material C are added to the component A of the island region (2); The preparation method of the solvent-based ceramic comprises the following steps: stirring triethoxysilane, dimethyl sulfoxide and a catalyst to react, then adding ethoxyphenyl silicone resin, stirring and adding functional filler to obtain solvent-based ceramic; the catalyst is prepared by the following steps: placing 100 parts of octamethylcyclotetrasiloxane in a beaker, and placing the beaker in an oil bath; slowly adding 0.2-0.3 parts of potassium hydroxide into the beaker through a funnel, stirring and heating to 115-120° C., cooling to room temperature after the potassium hydroxide is completely dissolved to obtain a transparent potassium hydroxide alkali gel as a catalyst; the mass ratio of the triethoxysilane, ethoxyphenyl silicone resin and functional filler is 1:1:1.5; In the base region (1), the preparation process of component A is as follows: polyetheramine and polyaspartic acid ester resin are weighed separately and vacuum dried, nitrogen is introduced to cool down, diisocyanate is added dropwise, dimethyl sulfoxide is added after reaction and stirred to obtain component A; The preparation process of component B is as follows: the solvent-based ceramic and the substance C are mixed in a mass ratio of 0.1 to 0.35:1, and the component B is obtained after stirring; In the island area (2), the preparation process of component A is to weigh polyetheramine and polyaspartic acid ester resin respectively, vacuum dry them, introduce nitrogen to cool them down, drop diisocyanate and a mixture of solvent-based ceramic and substance C, add dimethyl sulfoxide after reaction and stir to obtain component A; wherein the mixing mass ratio of solvent-based ceramic and substance C is 0.1-0.2:1; The preparation process of component B is to mix the solvent-based ceramic and the substance C in a mass ratio of 0.3-0.6:1, and then stir to obtain component B.
2. The island-in-the-sea coating suitable for the leading edge of a wind turbine blade according to claim 1, characterized in that: The average diameter of the island regions (2) is 200-300 μm, and the distance between adjacent island regions (2) is 200-350 μm.
3. The island-in-the-sea coating suitable for the leading edge of a wind turbine blade according to claim 1, characterized in that: The area of the island region (2) in the coating is 20-30%.
4. A method for preparing the sea-island type coating according to claim 1, characterized in that: The following steps are involved: The base area (1) is printed by a base area printing head (4), and the island area (2) is printed by an island area printing head (3), the island area printing head (3) follows the base area printing head (4) for printing, and laser curing is performed after the base area (1) and the island area (2) are printed; The base region (1) and the island region (2) are both printed by pressure extrusion, and the extrusion feed ratio of component A to component B of the printer is 1:1 to 2.2:
1.
5. The method for preparing the sea-island type coating according to claim 4, characterized in that: The printing interval between the island area printing head (3) and the base area printing head (4) is less than 15 seconds.
6. The method for preparing the sea-island type coating according to claim 4, characterized in that: The laser curing time of the base area (1) is 10 to 15 seconds, and the laser curing time of the island area (2) is 20 to 40 seconds.
7. The method for preparing the sea-island type coating according to claim 4, characterized in that: The molar ratio of -NCO in substance C to -NH in the polyaspartic acid ester resin in component A is (0.9~1.2):1.
Citation Information
Patent Citations
Wind turbine blade leading edge protective coating and preparation method thereof
CN112143302A
Wind turbine blade leading edge protection material, preparation method and application thereof
CN112143367A